The uses used in the political implications of Arabic-speaking foreign website - Matar, Iman Sabih; Ibrahim Al Falahi, Hussein Ali (ALBAHITH ALALAMI, 2018)
This research is intended to high light the uses of political content in foreign Arabic / speaking websites, such as “ CNN “ and” Euro News“, The research problem stems from the main question: What is the nature of the use of the websites in the political content provided through them? A set of sub-questions that give the research aspects and aims to achieve a set of objectives , including the identification of topics that included , the political content provided through , the sample sites during the time period for analysis and determine that the study uses descriptive research based on the discovery of the researcher, describing it accurately and defining the relations between the components. The research conducted the descriptive survey method, it is an analytical approach, which provides access to the required data ,and information that provided answers to research questions, the research methodology required the use of content analysis tool , which provided analytical political content provided through the sample sites to identify the inclination which was used in these content was divided into three topics dealt with the first methodological framework of the research dealt with the second types of inclinations used in the political implications of the websites while the third sections specialized in the results of the analytical study and reached the search to a set of conclusions , the most prominent of which is the following , focusing on the contents of the political implications presented in both locations depending in the first place on the situation in the Arab region , especially the Qatari crisis with the Gulf states and the adoption of both locations of the three basic types of inclinations implicated in the political content presented through them , namely , rationality and intimidation with clear contrast in their use with in each of the site sample , as the site of CNN has relied primarily on emotional inclinations that address the conscience while the site of Euro News clearly based on intimidation, zero 0